LC‐MS/MS determination of 1‐O‐acetylbritannilactone in rat plasma and its application to a preclinical pharmacokinetic study. (31st August 2015) - Li, Huajun; Li, Wei; Yu, Min; Jiang, Ligang
Abstract: A novel, rapid and sensitive LC‐MS/MS method for the determination of 1‐ O ‐Acetylbritannilactone (ABL), a sesquiterpene lactone abundant in Inula britannica, was developed and validated using heteroclitin D as internal standard. Separation was achieved on a reversed phase Hypersil Gold C18 column (50 × 4.6 mm, i.d., 3.0 µm) using isocratic elution with methanol–5 mM ammonium acetate buffer aqueous solution (80:20, v/v) at a flow rate of 0.4 mL/min. Calibration curve was linear ( r > 0.99) in a concentration range of 1.60–800 ng/mL with the lower limit of quantification of 1.60 ng/mL. Intra‐ and inter‐day accuracy and precision were validated by relative error (RE) and relative standard deviation (RSD) values, respectively, which were both less than ±15%. The validated method has been successfully applied to a pharmacokinetic study of ABL in rats. The elimination half‐lives were 0.412 ± 0.068, 0.415 ± 0.092 and 0.453 ± 0.071 h after a single intravenous administration of 0.14, 0.42, and 1.26 mg/kg ABL, respectively. The area under the plasma concentration–time curve from time zero to the last quantifiable time point and from time zero to infinity and the plasma concentrations at 2 min were linearly related to the doses tested. Copyright © 2015 John Wiley & Sons, Ltd.